Contactless blood pressure monitoring with IR-UWB radar - Puah, Aaron Chin How (Nanyang Technological University, 2024)
This project aims to utilize an Impulse-Radio Ultra-wideband (IR UWB) radar for a continuous and non-invasive monitoring method of blood pressure(BP).Although BP is a critical indicator of health conditions, traditional methods of measurements are restrictive and inconvenient. By leveraging the ability of the IR UWB radar to detect very subtle movements, this project aims to measure the blood pressure of the subject.